В. В. Латышев: опыт каталогизации крымских эпиграфических памятников - Непомнящий, А.А. (Праці Центру пам’яткознавства, 2013)
Рассмотрен вклад выдающегося российского антиковеда Василия Васильевича Латышева (1855–1921) в изучение античного периода истории Крыма, систематизацию и публикацию эпиграфических памятников. Проанализирована роль В. В. Латышева в изучении древней и средневековой истории Крыма, в особенности, источниковой базы исследования. Розглянуто внесок видатного російського вченого Василя Васильовича Латишева
(1855–1921) у вивчення античного періоду історії Криму, систематизацію і публікацію епіграфічних пам'яток. Репрезентовано внесок В. В. Латишева у вивчення давньої та середньовічної історії Криму, особливо, джерельної бази дослідження. The article describes the contribution of the prominent Russian antiquity scientist Vasily
Latyshev (1855-1921) to the studing of the ancient period of the history of the Crimea,
organizing and publishing epigraphic monuments. In this paper the role of
V.V. Latyshev in the studing of ancient and medieval history of the Crimea, in particular,
the source base of the study. It is emphasized that published monuments epigraphic is the
most fundamental body of published written sources on the history of the ancient period
of the Crimea to the present time. It is noted that due to methodological assistance provided
by the local research scientist forces has been tremendous progress in the studying
of the ancient monuments in Kerch museum (K.E. Dumberg, V.V. Shkorpil) and Chersonese
(K.K. Kosciusko-Valyuzhinich, L.A. Moses), there have been numerous publications
of local regional specialists dedicated to exploring and transcripts of the Crimean
inscriptions (K.K. Kosciusko-Valyuzhinich, V.V. Shkorpil). Based on the studing of V.V.
Latyshev correspondence it is shown that an important form of the Crimean study activities
were his constant contact with local and regional specialists of Crimean studies and
scientists from other research centers.